32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-2012
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Aircraft Design Methodology using ADAS Linked to CEASIOM

Abstract: The aircraft design stages, conceptual and preliminary, are necessarily collaborative by their very nature. An example design carried out in this paper brings the collaborative aspects of design to life by two academic groups, one in Naples and one in Stockholm, using their own tools ADAS and CEASIOM, working respectively on conceptual and preliminary design. The ADAS tool is primarily empirically-based design methodology, and the CEA-SIOM tool is primarily physics-based design methodology. The example chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Zhang et al (2014) showed a thrust effect on lift and pitching moment through CFD Eulerian simulation on a new commuter aircraft, highlighting the lift and longitudinal stability increment.…”
Section: Introductionmentioning
confidence: 92%
“…Zhang et al (2014) showed a thrust effect on lift and pitching moment through CFD Eulerian simulation on a new commuter aircraft, highlighting the lift and longitudinal stability increment.…”
Section: Introductionmentioning
confidence: 92%
“…Extensive use of this environment has been made and a broad list of publications are available demonstrating the capability of the environment. [28][29][30][31][32][33][34][35] Desktop Aeronautics developed the program for aircraft synthesis studies (PASS). 36 It is suited for conventional subsonic layouts, but is also capable of analyzing supersonic business jets or oblique wings.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable example is the ADAS software developed at University of Naples (Nicolosi and Paduano, 2011) mainly for teaching purposes. Another interesting example of software developed in academia is given by the CEASIOM framework which has been also used in combination with the ADAS software (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%